Political science, science, and professionalization: Indonesia and its development: Ilmu politik, sains, dan profesionalisasi: Indonesia dan perkembangannya - M Faishal Aminuddin; Makhasin, Luthfi; Permana, Panji Anugrah (Universitas Airlangga, 2025)
Political science, as a developing discipline, continues to spark debates regarding its scientific foundations. Its expansion into professional and practical domains has yet to establish universally applied standards. This article discusses the dynamics and development of political science by analyzing its scientific basis, areas of study, and historical trajectory. More specifically, it highlights the discipline’s growth in Indonesia. As a relatively young field of study, its development in the democratic era offers hope for the consolidation of political science as a discipline with clearer standards, contributions, and directions for advancement that are connected to global dynamics.